Internalization of Faith Educational Value in the Humanistic Perspective Riko Animation Series - M. Ali Sibram Malisi; Fauziyah Fauziyah; Surawan Surawan (AL-ISHLAH: Jurnal Pendidikan, 2023)
Faith is the foundation of a building in Islam, someone who has strong faith will carry out worship in an orderly manner, have noble morals and behave well. To form a pious human personality, education is needed on the basis of faith. Strong faith will become a stronghold for unwanted values to be internalized. Faith education can be instilled through technology such as film. Among the films that can be used as learning media is Riko The Series, which is produced by Garis Ten Corporation.This study attempts to describe and analyze the film Riko the Series in internalizing the value of faith in Allah SWT and a humanistic view of the value of faith in Allah SWT in the film Riko the Series. This study uses a type of research library research by using the semiotic analysis technique of Roland Barthes theory. The results of the study show that: 1) The value of faith in Allah SWT contained in the Riko The Series film is grouped into three, namely: the value of doing good and compassion, the value of forgiveness, and the value of muhasabah which is pursued through several sequential and systematic stages, namely the stage transformation, transaction stage, and transinternalization stage which generally uses the advice method, the exemplary method, the habituation method, and the targhib method.